Sobre cuatro ontologías inmanentes en Gilles Deleuze, en el cruce de La imagen-movimiento y Diferencia y repetición - Ferreyra, Julián (2023)
By serially arranging Difference and Repetition (1968) and The Movement Image (1983) this paper sketches four trails in Gilles Deleuze’s divergent ontology, showing how each of the montage schools of classical cinema implies a determinate inversion in relation to four facets of the philosophical tradition represented by Hume, Spinoza, Hegel and Descartes. The taxonomy of the cinema studies opens clear paths in Deleuze’s obscure ontology. The book of 1968 reveals the philosophical load implicit in the cinematographic developments; at the same time, it shows the divergencies and incompatibilities that growl under the apparent neatness of the classification of cinematographic images.